SISTEM PELAYANAN JUAL BELI ONLINE MELALUI MEKANISME DROPSHIPPING DALAM PERSPEKTIF BISNIS ISLAM - Ilmi Elbas, Bangga Yama; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Buying and selling online is a technological development that makes it easier for sellers and buyers to carry out buying and selling activities. Especially for sellers who make it easier to market their products with many buying and selling facilities such as dropshipping. Dropshipping is a way of selling that does not require capital and all packaging and shipping activities are carried out by the supplier. This study aims to determine the online buying and selling service system through the dropshipping and the view of Islamic business on the system. The object of this research is Casco Store Mojokerto using descriptive qualitative method with purposive sampling technique. In collecting data, this study used primary and secondary data with data collection techniques in the form of interviews and documentation. The data obtained were analyzed systematically and checked through triangulation so that it corresponds to the actual situation. This study resulted in the finding that Casco Store uses a dropshipping with direct payment schemes and on-site payments that are allowed in Islam.